Copper Iron Chalcogenide Semiconductor Nanocrystals in Energy and Optoelectronics Applications—State of the Art, Challenges, and Future Potential. Issue 8 (8th February 2023) - Bhattacharyya, Biswajit; Balischewski, Christian; Pacholski, Claudia; Pandey, Anshu; Bald, Ilko; Taubert, Andreas
Abstract: I‐III‐VI2 semiconductor nanocrystals have been explored in countless optoelectronics and green energy applications. While indium‐based compounds are arguably the best‐known variants of these semiconductors and have been widely studied for their photophysical properties, other I‐III‐VI2 semiconductors are emerging as serious competitors. This review focuses on the current state of the art and recent progress made in the research and technology of one of the most promising competitors to indium‐based I‐III‐VI2 semiconductor nanocrystals, CuFeS2 nanocrystals. CuFeS2 is a promising alternative to indium‐based systems, mostly because many properties are competitive and because iron is much more abundant than indium. Replacing In(III) with Fe(III) would thus significantly alleviate the issue of raw material availability. The article highlights new synthesis approaches and summarizes and discusses advanced optical properties including surface plasmon resonance and luminescence properties. Moreover, potential applications in thermoelectric, photodetection, photothermal, and photovoltaics are illustrated and discussed. Finally, future perspectives for materials development, upscaling, and application in new processes and devices, such as self‐assembly, patterning, or plasmonic catalysis, are presented as well. Abstract : This review summarizes recent advances in CuFeS2 semiconductor nanocrystal research and applications. Key synthetic methods and the most prominent structural and optical characteristics along with potential applications are discussed. Finally, the prospects of CuFeS2 as an earth abundant infrared bandgap material for large scale applications and some challenges associated with the larger scale production of these materials are introduced as well.